SUPERVISI KEPALA SEKOLAH UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DI SD NEGERI PULAU RIMAU - Son Haji (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The focus of this study is: (1). The strategy of supervising the school principal to improve the pedagogical competence of teachers at SDN 1 Pulau Rimau, (2). Approach to supervising the principal to improve teacher pedagogical competence at 1 Rimau Island Elementary School. (3). The implication of supervising the principal is to improve the pedagogical competence of teachers at SDN 1 Pulau Rimau. This type of research is qualitative research. The technique used by researchers is collecting data usingobservation, interviews and documentation studies.: (1). The principal's supervisory strategy to improve teacher pedagogical competence through the implementation of effective academic supervision with conceptual (a) skills; (b) interpersonal; and (c) technical. (2). Approach to the principal's supervision to improve the pedagogical competence of the teacher. The approach used (a) Directif Approach; (b) Non directive approach; and (c) Collaborative Application. (3) Implications for schools namely the creation of a conducive school atmosphere. the creation of effective learning by applying interesting learning methods, the implementation of a curriculum that is in and accordance with the standards.